Development of a co‐designed, evidence‐based, multi‐pronged strategy to support normal birth. (13th April 2022) - Allen, Jyai; Toohill, Jocelyn; Creedy, Debra K.; Callander, Emily J.; Gamble, Jenny
Abstract: Australia's caesarean section (CS) rate has been steadily increasing for decades. In response to this, we co‐designed an evidence‐based, multi‐pronged strategy to increase the normal birth rate in Queensland and reduce the need for CS. We conducted three workshops with a multi‐stakeholder group to identify a broad range of options to reduce CS, prioritise these options, and achieve consensus on a final strategy. The strategy comprised of: universal access to midwifery continuity‐of‐care and choice of place of birth; multi‐disciplinary normal birth education; resources to facilitate informed decision‐making; respectful maternity care and positive workplace culture; and establishment of a Normal Birth Collaborative.